Development of carbon nanotube-aluminium nanocomposite for brake disc application - Abdullahi, Umma (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
A light weight carbon nanotube-aluminium (CNT-Al) nanocomposite with improved tribo-mechanical properties can be a potential replacement material for the brake disc application. CNT-Al nanocomposites with four different concentrations of 1, 1.5, 2 and 2.5 wt% CNT were successfully fabricated using powder metallurgy route. Ball milling parameters such as preliminary mixing of CNT and Al in a tube via manual hand shaking and process control agent (PCA) were considered for the homogeneous and uniform dispersion of CNT in aluminium matrix with lower milling time. The characterization of CNT-Al mixed powder and CNT-Al nanocomposite were performed using SEM, FESEM, EDX and XRD analyzer. Density was measured using a digital densitometer and compared with the theoretical density. The mechanical properties were investigated using universal testing machine, Vickers micro hardness tester and nanoindentation machine. The wear test on the nanocomposite was carried out at two different test parameters such as normal applied load and sliding speed using a universal pin-on-disc tribo machine. The study of the wear morphology after the wear test was performed using SEM and Wyco surface profilometer. The morphology of the fabricated CNT-Al nanocomposite showed uniform and homogeneous dispersion of CNT into Al matrix. Evidence of elemental mapping and line analysis with significant reduction of milling time also confirmed that CNT was homogeneously distributed in Al matrix. The physio-mechanical properties showed that 1.5 wt% CNT was the optimum concentration as it showed highest value of compressive strength, micro and nano hardness. A distinctive abrasive and adhesive wear were observed from the morphological image of the wear worn surface. The wear test results also showed that 1.5 wt% CNT-Al nanocomposite has the lowest value of wear rate compared to other nanocomposites. The coefficient of friction of 1.5 wt% CNT-Al nanocomposite showed lower and stable friction coefficient at different normal loads and speeds. A wear mechanism map was developed and it served as a tool which identified and displayed regimes for different types of wear including the transition for CNT-Al nanocomposite material. In order to evaluate the fabricated CNT-Al nanocomposite, Design of Experiment (DOE) was employed for the development of empirical model of physio-mechanical and wear properties. The developed empirical models adequately and significantly fitted to justify the accuracy of the experimental results. The DOE confirmed that 1.5 wt% CNT showed better physio-mechanical and wear properties of the CNT-Al nanocomposite. The interaction of two factors at a time via the surface plots also revealed that 1.5 wt% CNT is the optimum concentration among the four generated concentrations. This 1.5 wt% CNT is found to be the potential light weight CNT-Al nanocomposite for brake disc application.